Evaluation of the knowledge of the issues related to human papillomavirus infections within young women - Węgorowski, Paweł; Michalik, Joanna; Turkowska, Karolina; Stanisławek, Andrzej; Wolski, Dariusz; Bieńko, Marek; Radzki, Radosław P. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Human papillomavirus infections are frequent in on average 9% to 13% of the female population, and the risk of infection throughout life exceeds 50%. The HPV virus causes changes in the mucous membranes and the skin of the genital area in both women and men. Aim. This paper presents epidemiology, prophylaxis, diagnostics and treatment of HPV and cervical cancer infections. In addition, the knowledge of issues related to human papillomavirus infection among young women was assessed. Materials and methods. The diagnostic survey method was used to carry out the research. The research tool was a questionnaire of own authorship consisting of 41 questions. The research group consisted of 240 women. The research was carried out from June to September 2016 at the Chodźki Medical Center and the Luxmed facility in Lublin. Results. There is a relationship between the education of the respondents and their knowledge about the human papillomavirus infection. The studies did not show a significant relationship between the self-esteem of the studied women and whether they were vaccinated against the HPV virus (Chi-square = 0.362, p = 0.547). Conclusions. The general level of knowledge on issues related to human papillomavirus infection among young women is at the secondary level. A higher level of general knowledge was shown by women with better education, related to the medical and biological sciences. The self-assessment of the respondents coincides with the general knowledge, based on detailed questions, on issues related to HPV infection. Promoting knowledge about HPV infection is unsatisfactory.
Keywords: HPV virus; human papillomavirus; cervical cancer